Gender Stratified Monopoly: Why Do I Earn Less and Pay More? - Smith, Stacy L. (My University, 2017)
A modified version of Monopoly has long been used as a simulation exercise to teach inequality. Versions of Modified Monopoly (MM) have touched on minority status relative to inequality but without an exploration of the complex interaction between minority status and class. This article introduces Gender Stratified Monopoly (GSM), an adaptation that can be added to existing versions of MM as a step toward such a conversation. I draw on written student reflections and observations from five test courses over two years to demonstrate the effectiveness of GSM. Data indicate student recognition of the female status as more economically challenging and less “fair” relative to the male status, with real-world consequences.
Citation: Smith, Stacy L. 2017. “Gender Stratified Monopoly: Why Do I Earn Less and Pay More?” Teaching Sociology 45(2):168-76.
Keywords: Active learning; Gender; Inequalities; Simulation; Social Class